Modern philosophical conceptions of social institutions - Shpyljova, Anastasiya (Actual Problems of Mind, 2017)
The author brieﬂy describes the current philosophical conceptions of social institutions of E. Durkheim, T. Parsons, T. Veblen, D. North and J. Searle and compares fundamental positions of the listed philosophers.